Penyimpangan Ortografi Bahasa Jawa pada Media Sosial Instagram - Sabbihisma Debby Satiti; Hendrokumoro Hendrokumoro (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
Language deviations can seriously impact language rules and norms. Language deviations in non-formal texts can impact the production of formal texts. This study attempts to examine the orthographic deviations of the Javanese language in non-formal texts taken through Instagram. This study aims to describe the forms of orthographic deviations on social media. The data of this research are in the form of deviations at the orthographic levels obtained from the data source, namely Instagram through the @dagelan_jowo account. Documentation techniques collected the data. The data obtained were analysed descriptively qualitatively. The results showed that orthographic deviations consisted of phonological spelling errors, errors in capital letters, foreign languages, punctuation marks, and errors in the use of numbers. Based on these findings, it can be concluded that there are still negative attitudes found by Javanese speakers towards their language, as evidenced by the many deviations of Javanese language in both formal and non-formal texts.